FeNi Layered Double‐Hydroxide Nanosheets on a 3D Carbon Network as an Efficient Electrocatalyst for the Oxygen Evolution Reaction. (25th January 2016) - Li, Yang; Zhao, Mengjia; Zhao, Yang; Song, Long; Zhang, Zhipan
Abstract : An efficient electrocatalyst for oxygen evolution has been prepared via the deposition of iron–nickel layered double‐hydroxide (FeNi‐LDH) nanosheets on 3D carbon network as the building scaffold in a one‐step hydrothermal process. It is found that upon the assembling of FeNi‐LDH nanosheets with graphene into the 3D cross‐linked hybrid, the FeNi‐LDH/graphene hybrid features a well‐improved catalytic activity towards the oxygen evolution reaction (OER) with a good stability during the long‐term cycling experiment. Moreover, the hybrid catalyst is also active in the oxygen reduction reaction (ORR), qualifying it as a new type of bifunctional catalyst that can work in metal–air batteries. Abstract : An electrocatalyst that can effectively catalyze the oxygen evolution reaction is prepared via the deposition of iron–nickel layered double‐hydroxide (FeNi‐LDH) nanoplates on a 3D carbon framework as the building scaffold in a one‐step hydrothermal process. The catalyst is also active in the oxygen reduction reaction, making it a new type of bifunctional catalyst for metal–air battery applications.